Developing a sustainable missionary programme for black South African churches : an analysis of the role that churches in black community are playing in terms of their missionary obligation - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2008.